SH3KBP1 Promotes Glioblastoma Tumorigenesis by Activating EGFR Signaling - Song, Hai; Wang, Yanpei; Shi, Chaojia; Lu, Jianxiang; Yuan, Tian; Wang, Xiangpeng (Frontiers in Oncology, 2021)
Glioblastoma (GBM) is the most common and aggressive brain tumor in adults. Overexpression or activation of epidermal growth factor receptor (EGFR) occurs commonly in multiple human cancers and promotes tumorigenesis. However, the underlying molecular mechanism of EGFR aberrant activation and the downstream signaling pathways remains largely unknown. In this study, we report that both SH3-domain kinase binding protein 1 (SH3KBP1) mRNA and protein levels are highly expressed in GBM and its high expression is associated with worse survival of glioma patients. In addition, we provide evidence that SH3KBP1 is prominently expressed in GBM stem cells (GSCs) and have potential to serve as a novel GSCs marker. Moreover, silencing SH3KBP1 dramatically impairs GBM cell proliferation, migration and GSCs self-renewal ability in vitro and xenograft tumors growth in vivo. Most importantly, we found that SH3KBP1 directly interacts with EGFR and may act as an adaptor protein to transduce EGFR signaling. Together, our work uncovers SH3KBP1 as a novel regulator of oncogenic EGFR signaling and also as a potential therapeutic target for GBM patients with EGFR activation.